An exploration into the problematic public policies and the leadership challenge for socio-economic transformation in South Africa. Issue 1 (10th June 2019) - Ndalamba, Ken Kalala
Abstract : Purpose: This paper aims to explore the problematic of public policies and leadership challenges for socio-economic transformation in South Africa. The paper illustrates that policies and laws of socio-economic reform have been introduced in democratic South Africa. However, socio-economic transformation remains a challenge. Lack of trust in the leadership relationships amongst political and economic agents is pointed as a contributing factor. Hence, LE emerges as a leadership strategy to help mitigate the problem. Design/methodology/approach: The paper starts by presenting the current economic situation of South Africa touching on some important economic indicators to illustrate the consequences of poor leadership in public policy implementation process. The paper then analyses the leadership challenges to drive socio-economic reforms that have been introduced in South Africa since the end of apartheid with focus on the current National Development Plan. Lack of trust in leadership is identified as a problematic factor and leadership ethos (LE) emerges as a leadership strategy to enable the building of trust in leadership for the purpose of a successful implementation of public policies. Findings: Lack of trust in leadership is identified as a problematic factor contributing in the absence of cooperation and collaboration in the leadership relationship amongst public servants (from up to bottom) and citizens for the purpose of successful implementation of public policies. Hence, there is need for a new leadership paradigm that would enable the building of trust in these leadership relationships. LE emerges as such a leadership strategy. Practical implications: The paper calls for an exploration into the understanding and practice of LE and its inherent critical success factors (CSFs) considered as a leadership strategy that can help drive particularly public policies implementation process. LE intends to promote moral leadership that helps public servants to build good character and thus the will to do the right thing, and mutually trusting relationship is a CSF of LE. Therefore LE enables build the much needed trust in leadership relationships for a successful organisational leadership and management. Originality/value: This paper provides significant implications by identifying lack of trust as a problematic factor in the leadership relationships amongst political and economic agents in South Africa, contributing thus in the poor implementation of public policies. LE emerges as a leadership strategy that would help mitigate the problem by enabling the building, the maintenance and restoration of trust in organisational and or institutional management for a successful public policy implementation process.